FRET-detectable interactions between the ARE binding proteins, HuR and p37AUF1 - David, Pamela S. (Cold Spring Harbor Laboratory Press, 2007)
A number of highly regulated gene classes are regulated post-transcriptionally at the level of mRNA stability. A central feature in these mRNAs is the presence of A+U-rich elements (ARE) within their 3′ UTRs. Two ARE binding proteins, HuR and AUF1, are associated with mRNA stabilization and destabilization, respectively. Previous studies have demonstrated homomultimerization of each protein and the capacity to bind simultaneous or competitively to a single ARE. To investigate this possibility further, cell biological and biophysical approaches were undertaken. Protein–protein interaction was monitored by fluorescence resonance energy transfer (FRET) and by immunocytochemistry in live and fixed cells using fluorescently labeled CFP/YFP fusion proteins of HuR and p37AUF1. Strong nuclear FRET between HuR/HuR and AUF1/AUF1 homodimers as well as HuR/AUF1 heterodimers was observed. Treatment with the MAP kinase activator, anisomycin, which commonly stabilizes ARE-containing mRNAs, caused rapid nuclear to cytoplasmic shuttling of HuR. AUF1 also underwent shuttling, but on a longer time scale. After shuttling, HuR/HuR, AUF1/AUF1, and HuR/AUF1, FRET was also observed in the cytoplasm. In further studies, arsenite rapidly induced the formation of stress granules containing HuR and TIA-1 but not AUF1. The current studies demonstrate that two mRNA binding proteins, HuR and AUF1, are colocalized and are capable of functional interaction in both the nucleus and cytoplasm. FRET-based detection of AUF1/HuR interaction may serve as a basis of opening up new dimensions in delineating the functional interaction of mRNA binding proteins with RNA turnover.